EVALUATION OF DENTAL DISCOLORATION CAUSED BY FILLING PASTES IN PRIMARY TEETH (CIPEEX, 2024)
The aim of this research project was to evaluate the dental discoloration caused by filling pastes used in pediatric dentistry. Blocks of bovine lower incisor crowns were prepared, leaving a 2 mm thick enamel and dentin remnant. The blocks were randomly assigned into 2 groups, according to the presence or absence of dentin hybridization. After hybridization, the blocks were further subdivided into 5 experimental groups based on the type of endodontic cement: 1) Guedes Pinto Paste; 2) Zinc oxide-eugenol paste; 3) Calcium hydroxide paste, prepared with calcium hydroxide and propylene glycol; 4) Paste containing Chloramphenicol + tetracycline chloride + zinc oxide-eugenol; 5) Vitapex®. Color determination was performed using a digital spectrophotometer, and measurements were obtained at 7, 30, and 60 days after the material placement. Data related to discoloration were tabulated and tested for normality using the Shapiro-Wilk test. ANOVA and Tukey tests were used for analysis. Both the filling paste and evaluation period showed statistical differences in color alteration (p < 0.05). Endodontic pastes induce staining of the dental structure.
Keywords: Pediatric dentistry; dental discoloration; dentin bonding agents